2023
DOI: 10.1096/fj.202201202rr
|View full text |Cite
|
Sign up to set email alerts
|

miR‐124‐3p improves mitochondrial function of renal tubular epithelial cells in db/db mice

Abstract: Diabetic kidney disease (DKD) is one of the most serious complications of diabetes mellitus (DM) and the main cause of end‐stage renal failure. However, the pathogenesis of DKD is complicated. In this study, we found that miR‐124‐3p plays a key role in regulating renal mitochondrial function and explored its possible mechanism in DKD progression by performing a series of in vitro and in vivo experiments. Decreased expression of miR‐124‐3p was found in db/db mice compared to db/m mice. Moreover, miR‐124‐3p down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“… 15 Under conditions of high glucose and high lipid, downregulation of miR-124-3p can induce FOXQ1 in renal tubular epithelial cells, thereby inhibiting SIRT4, leading to mitochondrial dysfunction, and promoting the occurrence of diabetic nephropathy. 33 In our experiments, we found that KLF6 silence could mitigate mitochondrial dysfunction in CSE-induced BEAS-2B cells through SIRT4 upregulation.…”
Section: Discussionmentioning
confidence: 54%
“… 15 Under conditions of high glucose and high lipid, downregulation of miR-124-3p can induce FOXQ1 in renal tubular epithelial cells, thereby inhibiting SIRT4, leading to mitochondrial dysfunction, and promoting the occurrence of diabetic nephropathy. 33 In our experiments, we found that KLF6 silence could mitigate mitochondrial dysfunction in CSE-induced BEAS-2B cells through SIRT4 upregulation.…”
Section: Discussionmentioning
confidence: 54%
“…FoxQ1 (up-regulated in H vs C, while down-regulated in HM vs H) is a member of forkhead box transcription factor family [ 29 ]. Liang et al found that expression of FoxQ1 was elevated in renal tubular epithelial cells under high-glucose, high-lipid conditions, and FoxQ1 inhibited Sirt4 expression, leading to mitochondrial dysfunction and promoting the development of DKD [ 30 ]. In addition, FoxQ1 is recognized as a driver of epithelial-mesenchymal transition (EMT) and metastasis in multiple cancer types [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yi et al have illuminated that the upregulation of SIRT4 in keratinocytes alleviates the senescence phenotype 28 . Furthermore, Liang et al have substantiated that the downregulation of SIRT4 exacerbates mitochondrial damage in renal tubular epithelial cells 29 . Additionally, Dai et al have unveiled the suppressive effect of SIRT4 on the inflammatory response in OA 30 .…”
Section: Ivyspringmentioning
confidence: 99%